Khởi nghiệp đổi mới sáng tạo gắn với tự tạo việc làm: nghiên cứu đối với sinh viên năm cuối tại một số trường đại học - Phạm Xuân Thu, Phạm Xuân Thu; Phan Thị Hằng, Phan Thị Hằng; Bùi Thị Bích Thủy, Bùi Thị Bích Thủy; Đào Ngọc Phương, Đào Ngọc Phương (Tạp chí Giáo dục, 2025)
In the context of globalization and digital transformation, innovative entrepreneurship has become a key driver of socio-economic development, requiring a supportive ecosystem for university students, who represent a young intellectual group with strong creative potential. Recognizing this, the Government has introduced various policies to promote entrepreneurial mindsets and support students in creating their own employment. This article examines the challenges faced by students in innovative entrepreneurship associated with self-employment, based on case studies conducted in three localities: Ho Chi Minh City, Hanoi, and Da Nang. These findings provide an important foundation for identifying the underlying causes of current limitations and proposing feasible solutions to overcome challenges and promote innovative entrepreneurship linked to self-employment among Vietnam’s young intellectuals, thereby informing more effective policies and support initiatives in the future.